Farmers' Characteristics Associations with the Knowledge for Sheep Estrus Detection in Batur Village, Banjarnegara, Indonesia - Alek Ibrahim; Wayan Tunas Artama; Rini Widayanti; Bayu Andri Atmoko; I Gede Suparta Budisatria; Dyah Ayu Larasati (Jurnal Sain Veteriner, 2022)
The accuracy of the estrus detection was important in sheep breeding management. This study aimed to determine the correlation between the farmers’ characteristics and the knowledge on estrus detection of their sheep. The data were collected by interviewing 33 farmers, who have raised sheep with a breeding system for at least two years of experience in Batur Village, Banjarnegara, Indonesia. The farmers’ knowledge for estrus detection was divided into three-level, namely low, medium, and high levels. The results showed that the farmers’ knowledge for estrus detection was 51.5%, 27.3%, and 21.2% on the low, medium, and high levels, respectively. There was a significant relationship between formal education, informal education, number of sheep, the sheepfold position, stay duration in the sheepfold, and the ram ownership for mating toward knowledge of estrus detection level. It can be concluded that there is a relationship between farmer characteristics in Batur Village and the ability to detect estrus in ewes, which is dominated at low levels, so it is necessary to increase farmers' knowledge regarding estrus detection.